1993
DOI: 10.2190/n2gw-n9we-ueup-9h4d
|View full text |Cite
|
Sign up to set email alerts
|

Reactions to the Death of a Parent during Midlife

Abstract: Interviews with eighty-three adults aged thirty-five to sixty who had lost a parent one to five years previously found that 60 percent continued to experience emotional reactions and 44 percent continued to experience somatic reactions to the death. The majority also reported changes in their sense of maturity, personal priorities, work and/or career objectives, feelings about their own mortality, and the importance and nature of various social relationships. These impacts generally corresponded to development… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
25
0
1

Year Published

1996
1996
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(29 citation statements)
references
References 20 publications
3
25
0
1
Order By: Relevance
“…Research on sibling relationships in parentally bereaved families has been contradictory, with some studies showing the benefit of having a sibling to share the tragic experience with (Hurd, 2002;Mack, 2004), and others showing the burden of having a sibling after the death of a parent (Connidis, 1992;Scharlach & Fredriksen, 1993). When the death of a parent occurs in childhood, the effect on siblings can be complicated, as some sibling relationships will experience positive outcomes while others will experience negative ones (Ross & Milgram, 1982).…”
Section: Siblingsmentioning
confidence: 99%
See 1 more Smart Citation
“…Research on sibling relationships in parentally bereaved families has been contradictory, with some studies showing the benefit of having a sibling to share the tragic experience with (Hurd, 2002;Mack, 2004), and others showing the burden of having a sibling after the death of a parent (Connidis, 1992;Scharlach & Fredriksen, 1993). When the death of a parent occurs in childhood, the effect on siblings can be complicated, as some sibling relationships will experience positive outcomes while others will experience negative ones (Ross & Milgram, 1982).…”
Section: Siblingsmentioning
confidence: 99%
“…Hurd (2002) found that siblings can assist each other in grieving in a healthy way and avoiding depression; thus they become a very strong source of support, especially when the surviving parent is too preoccupied with his or her own grief. Parental death may result in siblings becoming closer and strengthening their sibling bonds (Hurd, 2002;Mack, 2004); however, the death may also create distance between the siblings, especially if the deceased parent occupied the role of kinkeeper in the family (Scharlach & Fredriksen, 1993).…”
Section: Siblingsmentioning
confidence: 99%
“…Research suggests an increase in conflict and a decline in relationship harmony are common among couples where a spouse is grieving over the loss of a parent (Umberson, 1995;Scharlach & Fredriksen, 1993).…”
Section: Midlife Marriagesmentioning
confidence: 99%
“…The death of a parent may constitute a dramatic shift in the lived experience of an adult offspring, and its significance has sparked the interest of many researchers (e.g., Abrams, 1999;Cait, 2005;Marshall, 2004;Moss & Moss, 2007;Petersen & Rafuls, 1998;Pope, 2005;Scharlach & Fredriksen, 1993). The death of a parent and the grief that follows may reverberate through many aspects of personal identity, affecting beliefs, ideas, values, and a diverse set of practices, such as pursuing a career, parenting, making financial investments, or planning for the impact of one's own eventual death.…”
Section: Introductionmentioning
confidence: 99%